DINAMIKA TUMBUH TANAMAN BAWANG MERAH (Allium cepa L. Kelompok Agregatum) VARIETAS LEMBAH PALU DENGAN PEMBERIAN PUPUK ORGANIK DAN INTERVAL PEMBERIAN AIR SISTEM SPRINGKLE - Esa wahyana; Muhammad Anshar; Andi Ete (Agroland: Jurnal Ilmu-ilmu Pertanian, 2017)
The objective of this study was to determine the dynamics of Lembah Palu shallot varietygrowth under various rates of organic fertilizer and different intervals of sprinkle watering systems. The research was conducted in Bulupountu Jaya village, SigiBiromarusub district, Sigi district of Central Sulawesi province from October to January 2014. The experiment was conducted using Split Plot design in which the main plots were watering intervals (one hour watering for every three days and one hour watering for every six days) and sub plots were 40 t/ha organic fetilizer applications (green leaf and manure bokashi).Plant parameters oberved were total leaf area, dry plant weight, net assimilation rate, relative growth rate and leaf area ratio.  The research results showed that there was no significant interaction effect between the watering intervals and the bokashi on the growth and yield of the shallots and individually the effect of the watering intervals was not significant as well.  Whereas, individually the bokashi was found to significantly affected the dry weight of Lembah Palu shallot variety plant at 40 days after planting. Keywords: Lembah Palu shallot, Organic fertilizers, and Watering.